Analysis on Wideband Channel Model for High Speed Wireless Communication Systems - Mon, Myint Myint; Tun, Hla Myo; Win, Lei Lei Yin; Win, Thanda; Aye, Mya Mya; Soe, Khaing Thandar; Pradhan, Devasis (Journal of Novel Engineering Science and Technology, 2025)
The paper emphasizes on the analysis on wideband channel model for high speed wireless communication systems. The research problem in this study are based on the following concepts such as (i) Firstly, it is necessary to change to the appropriate physical devices that can support 5G system, (ii) It is required to design a channel that will adapt to the medium that will be convenient for the changed physical devices, and (iii) Mobile terminals that currently use 4G cannot be used in 5G system. The objectives in this study are - to analyze the existing channel model for mobile communication, to analyze the mathematical and dynamical model for wireless propagation channel, to implement the wireless propagation channel with specific purposes, to implement the optimized channel model performance, and to evaluate the performance of the developed channel design. The numerical analyses in this study are conducted by using MATLAB language. The research direction in this study are based on the channel system functions, and tapped delay-line models. The simulation results are confirmed that the 12 taps in this study for the high speed wireless communication system design.